Nutrition Education for Pregnant Women Using Community-Based Approach for Stunting Prevention and Maternal and Child Health in Bulak Village, Surabaya City - utomo, bedjo; Soetjiatie, Liliek; Suprihatin, Kusmini; Intiyati, Ani (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
The pattern of people's eating culture is closely related to beliefs, taboos, taboos, and prohibitions on certain foods, so there is a feeling of concern in pregnant women not to eat certain foods. This kind of understanding requires education about nutritious food, for that the purpose of this service is to increase the knowledge and understanding of pregnant women about nutritious food so that mothers and babies are healthy. This activity method is carried out by means of seminars, training and assistance related to food counseling in accordance with the rules of nutrition without taboos and food taboos that develop in the community in accordance with their social and economic abilities with the target of pregnant women, stunted mothers under five toddlers, health cadres and PKK which focuses on 13 stunted children under five spread across 7 RWs in the Bulak District area. The results after providing training and mentoring activities to pregnant women for residents of Bulak Village, Surabaya City, the first health cadre and PKK is a change in a healthy diet, the second follows the recommendation of a balanced diet for pregnant women and breastfeeding mothers by applying